Antioxidant, thrombolytic, cytotoxic and membrane stabilizing activities and fatty acid composition of Acmella Calva (DC.) Flower - Rafi, Md Omar Sha; Shristy, Nusrat Tabassum; Mimi, Sauda Sultana; Chhanda, Sadia Afrin; Rahman, Md Hasanur; Rahman, Mohammad Sharifur; Rashid, Mohammad A; Muslim, Tanvir (Bangladesh Journal of Botany, 2025)
In the present study, crude methanolic extract (CRME) of A. calva flower along with its n-hexane (HSF), ethyl acetate (EASF), dichloromethane (DCMSF) and aqueous (AQSF) soluble fractions were subjected to antioxidant, thrombolytic, cytotoxic and membrane stabilizing activities. Fatty acid composition of the n-hexane extract was analysed by gas chromatography-flame ionization detector. None of the extracts showed any cytotoxicity against both carcinoma (HeLa) and normal cell lines (Vero and BHK-21). EASF scavenged the DPPH free radical most actively with IC50 value of 35.05 μg/ml. CRME and HSF showed profound membrane stabilizing activity by protecting human erythrocyte cell against hypotonic solution-induced and heat-induced lysis. CRME showed the highest (46%) clot lysis. Stearic acid (51.11%) and palmitoleic acid (39.38%) were found in the highest amount in both bound and free form of fatty acid, respectively. The observation from this study indicates the possibility of A. calva to be a good source of different bioactive phytochemicals. Bangladesh J. Bot. 54(3): 433-439, 2025 (September)